An intertidal life: Combined effects of acidification and winter heatwaves on a coralline alga (Ellisolandia elongata) and its associated invertebrate community. (July 2021) - Ragazzola, Federica; Marchini, Agnese; Adani, Mario; Bordone, Andrea; Castelli, Alberto; Cerrati, Gabriella; Kolzenburg, Regina; Langeneck, Joachim; di Marzo, Carlotta; Nannini, Matteo; Raiteri, Giancarlo; Romanelli, Elisa; et al.
Abstract: In coastal marine ecosystems coralline algae often create biogenic reefs. These calcareous algal reefs affect their associated invertebrate communities via diurnal oscillations in photosynthesis, respiration and calcification processes. Little is known about how these biogenic reefs function and how they will be affected by climate change. We investigated the winter response of a Mediterranean intertidal biogenic reef, Ellissolandia elongata exposed in the laboratory to reduced pH conditions (i.e. ambient pH – 0.3, RCP 8.5) together with an extreme heatwave event (+1.4 °C for 15 days). Response variables considered both the algal physiology (calcification and photosynthetic rates) and community structure of the associated invertebrates (at taxonomic and functional level). The combination of a reduced pH with a heatwave event caused Ellisolandia elongata to significantly increase photosynthetic activity. The high variability of calcification that occurred during simulated night time conditions, indicates that there is not a simple, linear relationship between these two and may indicate that it will be resilient to future conditions of climate change. In contrast, the associated fauna were particularly negatively affected by the heatwave event, which impoverished the communities as opportunistic taxa became dominant. Local increases in oxygen and pH driven by the algae can buffer the microhabitat in the algal fronds, thus favouring the survival of small invertebrates. Highlights: Coralline alga create a microhabitat with mitigating effect on ocean acidification. Temperature is the major driver of changes in the invertebrate reef community. Winter heatwaves and acidified conditions alter invertebrates community structure. Algal reef communities become dominated by opportunistic taxa.